2010
DOI: 10.1002/14651858.cd008654
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical policies: effects of restrictions on reimbursement

Abstract: BackgroundPublic policy makers and benefit plan managers need to restrain rising pharmaceutical drug costs while preserving access and optimizing health benefits. ObjectivesTo determine the effects of a pharmaceutical policy restricting the reimbursement of selected medications on drug use, health care utilization, health outcomes and costs (expenditures). Search methodsWe searched the 14 major bibliographic databases and websites (to January 2009). Selection criteriaIncluded were studies of pharmaceutical pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 42 publications
(2 reference statements)
1
41
0
Order By: Relevance
“…Nine reviews did not include any studies from low- or middle-income countries (Gilbody 2005; Fung 2008; Pariyo 2009; Green 2010; Nilsen 2010; Hayes 2012; Rashidian 2012; Acosta 2014; Grobler 2015), and four reviews only included studies conducted in low- or middle-income countries (Lagarde 2009; Prost 2013; Rockers 2013; El-Jardali 2015). Overall, 74% of the studies from the included reviews took place in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Nine reviews did not include any studies from low- or middle-income countries (Gilbody 2005; Fung 2008; Pariyo 2009; Green 2010; Nilsen 2010; Hayes 2012; Rashidian 2012; Acosta 2014; Grobler 2015), and four reviews only included studies conducted in low- or middle-income countries (Lagarde 2009; Prost 2013; Rockers 2013; El-Jardali 2015). Overall, 74% of the studies from the included reviews took place in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there are concerns expressed about the impact of economic evaluations in terms of fairness (25,26). This is why equity criteria have been introduced to balance public health decisions, namely to ensure fair distribution of health benefits in society (27). There is a particular need for public health decisions in terms of achievement of overall health policy goals, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another Cochrane review of 29 studies demonstrated that restrictions on reimbursement policies can improve prescribing in two ways [47]. First, restrictions targeting the newer, more expensive drugs can result in cheaper alternatives, equally effective medicines being used, without increased use of other services (as would be expected with any negative consequences of the restrictive policy).…”
Section: Perspectivementioning
confidence: 99%